THE DWARF PLANET 136199 HAUMEA AND ITS SATELLITES AND RINGS - Vidmachenko, Anatoliy (Collection of scientific papers «ΛΌГOΣ», 2025)
Haumea is the first of the dwarf planets discovered since the discovery of Pluto in 1930. However, its formal recognition as a dwarf planet was delayed for several years due to a dispute over who should be considered the discoverer of this celestial object. The first announcement of its discovery was made by a Spanish team led by José Luis Ortiz Moreno. When registering its discovery, the object was assigned the temporary designation "2003 EL61", according to the date of the image in which the object was found by the Spanish group. And only in September 2008 was the name of this object Haumea, proposed by the Americans, officially approved and included in the newly created in 2006 class of dwarf planets. It became the fifth dwarf planet and the fourth plutoid, along with Pluto, Eris and Makemake. In September 2006, Brown’s team submitted proposals for names based on Hawaiian mythology. At that time, (136108) 2003 EL61 and its two known moons were named after the deity of the island of Hawaii, where the Mauna Kea Observatory is located, in order to pay tribute to the area where these objects were discovered. Haumea is the goddess of fertility and childbirth; she had many children growing on different parts of her body. The two known moons at that time were named after Haumea’s two daughters: (136108) Haumea I Hiʻiaka and (136108) Haumea II Namaka. Hiʻiaka is about 310 km in diameter, has an orbital period of 48.9 days, and an orbital radius of 49,900 km. The satellite Namaka turned out to be about half as small (about 170 km); it orbits Haumea in an orbit with a semi-major axis of 25.6 thousand km with a period of about 18 days. It also turned out that Haumea has a narrow ring system. Photometric observations made by Brown’s group in 2005 using a telescope at the Keck Observatory revealed that Haumea rotates with a rotation period around its own axis of about 4 hours. The reason for the brightness fluctuation with an amplitude of about 0.28m may be the inhomogeneity of its surface, or an elongated shape. Simulations showed that the best fit is given by a model in the form of an ellipsoid with dimensions of 1960×1518×996 km with an average albedo of 0.73. Studies of Haumea’s spectrum in the 1.0-2.4 μm range, carried out in 2005 using telescopes at the Gemini and Keck observatories, revealed that its surface is covered mainly with crystalline water ice with grains with a diameter of 25-50 μm. Such crystalline ice forms at temperatures above 110 K, while the temperature on the surface of Haumea is always below 50 K, at which only ice in an amorphous state is formed. The spectra and color of Haumea’s surface indicate that this celestial object has recently undergone a "renovation" of its surface. Observations of the cover of the star by the dwarf planet Haumea on January 21, 2017, also revealed a ring around Haumea. It became the first ring discovered around a trans-Neptunian object. The ring has a radius of about 2287 km, a width of almost 70 km, and a transparency index of 0.5. It exists within the Roche limit of the dwarf planet Haumea.